Protection of female sex workers and social acceptance of female commercial sex workers in Indonesia - Rahma, Vivi Maulia; Fazrin, Fitriani; Tamba, Wahyu Pratama (Center for Sociological Studies and Community Developmen, 2025)
This article examines the social acceptance of female commercial sex workers in prostitution localities. Social acceptance is critical to their integration into the community. The research utilizes structuration theory to analyze the interplay between societal structures and individual agency in shaping community acceptance of these women. Data was collected through in-depth interviews with both community members living near the site and the sex workers themselves. The findings of the study reveal that the social relations between the community and localized prostitution emerge from the ongoing production and reproduction of social practices. These practices are produced by the community with the active participation of commercial sex workers. This social acceptance manifests itself in discursive and practical awareness, leading to the integration of sex workers into the social fabric. However, it's crucial to recognize that social acceptance alone is not enough to guarantee the protection of sex workers' rights. It must be accompanied by concrete efforts to ensure their fundamental rights. These include the right to health, safety, protection from violence and exploitation, and access to services and programs that promote their well-being.